The Application Of 4/3/2 Technique To Enhance Speaking Fluency Of EFL Students In Indonesia - Yufrizal, Hery (Advances in Social Sciences Research Journal, 2018)
The aims of this areticle are firstly to explore the application of 4/3/2 technique in enhancing learners’ speaking fluency and to exspose how fluency practie can help students’ improve their speaking ability. The research was conducted at a language school in Indonesia involving 20 first year students at the University of Lampung The students were divided into two teams the speaker team and the listener teams. The speaker team was given the opportunty to speak for three speaaking turns: four minutes, three minutes and two minutes. Later, the teams change roles the speakers become listeners, the listeners became speakers. The topics of the talks are determined by the group prior to the application or the actitivites. The results showed that students improve their speaking accuracy and fluency.during three speakiing turns.